150k views
5 votes
Please, I need help in this ??

Please, I need help in this ??-example-1
User Kunquan
by
6.0k points

1 Answer

3 votes

Answer:


\int(x^(4))/(x^(4) -1)dx = x + (1)/(4) ln(x-1) - (1)/(4) ln(x+1)-(1)/(2) arctanx + c

Explanation:


\int(x^(4))/(x^(4) -1)dx

Adding and Subtracting 1 to the Numerator


\int(x^(4) - 1 + 1)/(x^(4) -1)dx

Dividing Numerator seperately by
x^(4) - 1


\int 1 + (1)/(x^(4)-1 )\, dx

Here integral of 1 is x +c1 (where c1 is constant of integration


x + c1 + \int(1)/((x-1)(x+1)(x^(2)+1))\, dx----------------------------------(1)

We apply method of partial fractions to perform the integral


(1)/((x-1)(x+1)(x^(2)+1)) =
(A)/(x-1) + (B)/(x+1) + (C)/(x^(2) + 1)------------------------------------------(2)


(1)/((x-1)(x+1)(x^(2)+1)) = (A(x+1)(x^(2) +1) + B(x-1)(x^(2) +1) + C(x-1)(x+1))/((x-1)(x+1)(x^(2) +1))

1 =
A(x+1)(x^(2) +1) + B(x-1)(x^(2) +1) + C(x-1)(x+1)-------------------------(3)

Substitute x= 1 , -1 , i in equation (3)

1 = A(1+1)(1+1)

A =
(1)/(4)

1 = B(-1-1)(1+1)

B =
-(1)/(4)

1 = C(i-1)(i+1)

C =
-(1)/(2)

Substituting A, B, C in equation (2)


\int(x^(4))/(x^(4) -1)dx =
\int(1)/(4(x-1)) - (1)/(4(x+1)) -(1)/(2(x^(2)+1) )

On integration

Here
\int (1)/(x)dx = lnx and \int(1)/(x^(2)+1 ) dx = arctanx


\int(x^(4))/(x^(4) -1)dx =
(1)/(4) ln(x-1) -
(1)/(4) ln(x+1) -
(1)/(2) arctanx + c2---------------------------------------(4)

Substitute equation (4) back in equation (1) we get


x + c1 + (1)/(4) ln(x-1) - (1)/(4) ln(x+1) - (1)/(2) arctanx + c2

Here c1 + c2 can be added to another and written as c

Therefore,


\int(x^(4))/(x^(4) -1)dx = x + (1)/(4) ln(x-1) - (1)/(4) ln(x+1)-(1)/(2) arctanx + c

User Pojo
by
5.8k points